Use of 100 kV versus 120 kV in computed tomography pulmonary angiography in the detection of pulmonary embolism: effect on radiation dose and image quality - Gill, Maninderpal Kaur (Quant Imaging Med Surg, 2015)
OBJECTIVE: To determine the effective radiation dose and image quality resulting from 100 versus 120 kilovoltage (kV) protocols among patients referred for computed tomography pulmonary angiography (CTPA). METHODS: Sixty-six patients with clinical suspicion of pulmonary embolism (PE) were prospectively enrolled. Two CTPA protocols (group A: n=33, 100 kV/115 mAs; group B: n=33, 120 kV/90 mAs) were compared. Two experienced radiologists assessed image quality in terms of diagnostic performance and effect of artefacts. Image quality parameters [CT attenuation, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR)] and effective radiation dose between the two protocols were compared. RESULTS: The contrast enhancement in central and peripheral pulmonary arteries was significantly higher in group A than in group B (P<0.001) with the identical SNR (P=0.26), whereas the CNR was significantly higher in group A than in group B (P<0.001). The effective radiation dose for the 100 and 120 kV scans was 3.2 and 6.8 mSv, respectively. CONCLUSIONS: Reducing the tube voltage from 120 to 100 kV in CTPA allows a significant reduction of radiation dose without significant loss of diagnostic image quality.